A Mechanical Model of the Overlying Rock Masses in Undersea Coal Mining and a Stress-Seepage Coupling Numerical Simulation - Jie Fang; Lei Tian; Yanyan Cai; Zhiguo Cao; Jinhao Wen; Zhijie Wen (Advances in Civil Engineering)
The water inrush of a working face is the main hidden danger to the safe mining of underwater coal seams. It is known that the development of water-flowing fractured zones in overlying strata is the basic path which causes water inrushes in working faces. In the engineering background of the underwater mining in the Longkou Mining Area, the analysis model and judgment method of crack propagation were created on the basis of the Mohr–Coulomb criterion. Fish language was used to couple the extension model into the FLAC3d software, in order to simulate the mining process of the underwater coal seam, as well as to analyze the initiation evolutionary characteristics and seepage laws of the fractured zones in the overlying strata during the advancing processes of the working face. The results showed that, during the coal seam mining process, the mining fractured zones which had been caused by the compression-shear and tension-shear were mainly concentrated in the overlying strata of the working face. Also, the open-off cut and mining working face were the key sections of the water inrush in the rock mass. The condition of the water disaster was the formation of a water inrush channel. The possible water inrush channels in underwater coal mining are mainly composed of water-flowing fractured zones which are formed during the excavation processes. The numerical simulation results were validated through the practical engineering of field observations on the height of water-flowing fractured zone, which displayed a favorable adaptability.